The mediating effect of geospatial thinking on the relationship between family capital and academic achievement in geography - Zhang, Jianzhen; Su, Ting; Liang, Xiaoyu; Xu, Yanhua; Wang, Ziyang; Yu, Yuyao; Ge, Jiahao (Frontiers in Psychology, 2023)
Purpose: Family environment has the major impact on children’s academic development. The aim of this study was to research the relationship between family capital and academic achievement in geography. Further, geospatial thinking, as a form of spatial thinking focusing on the scale of the geographical environment, is closely related to family environment and academic achievement in geography. Thus, the study was more specifically to apply a mediation model to explore the potential mediating role of geospatial thinking. Methods: A total of 1,037 upper-secondary-school students in Western China were surveyed using t the Family Capital Questionnaire and the Geospatial Thinking Test Questionnaire. SPSS (version 26.0) was used for descriptive statistical analysis and correlation analysis. The PROCESS plug-in (version 4.0) was used to test the mediating effect of geospatial thinking. Results: (1) The correlation analysis showed that family capital has a positive effect on academic achievement in geography and is related to geospatial thinking. Moreover, geospatial thinking exerts a positive effect on academic achievement in geography. (2) The results of mediation analysis indicated that geospatial thinking plays mediating and buffering roles in the relationship between family capital and academic achievement in geography after controlling for family residence and gender. The direct and indirect effects accounted for 75.32% and 24.68% of the total effect, respectively. Conclusions: The results indicated that family capital not only affected academic achievement in geography directly but also indirectly through geospatial thinking. This finding provides some ideas for the development of geography education, which suggests that geography educators need to pay more attention to the influence of the family environment on students' geography learning in curriculum design and teaching processes. Also, the mediating role of geospatial thinking further uncovers the mechanisms underlying the academic achievement in geography. Therefore, it is necessary to focus on both students' family capital and geospatial thinking in the process of geography learning, and carry out more geospatial thinking training to improve academic achievement in geography.